Host-gut microbiota derived secondary metabolite mediated regulation of Wnt/β-catenin pathway: a potential therapeutic axis in IBD and CRC - Kumar, Sushma S.; Fathima, Ashna; Srihari, Preeti; Jamma, Trinath (Frontiers in Oncology, 2024)
The intestinal tract encompasses one of the largest mucosal surfaces with a well-structured layer of intestinal epithelial cells supported by a network of underlying lamina propria immune cells maintaining barrier integrity. The commensal microflora in this environment is a major contributor to such functional outcomes due to its prominent role in the production of secondary metabolites.Of the several known metabolites of gut microbial origin, such as Short Chain Fatty Acids (SCFAs), amino acid derivatives, etc., secondary bile acids (BAs) are also shown to exhibit pleiotropic effects maintaining gut homeostasis in addition to their canonical role in dietary lipid digestion. However, dysbiosis in the intestine causes an imbalance in microbial diversity, resulting in alterations in the functionally effective concentration of these secondary metabolites, including BAs. This often leads to aberrant activation of the underlying lamina propria immune cells and associated signaling pathways, causing intestinal inflammation. Sustained activation of these signaling pathways drives unregulated cell proliferation and, when coupled with genotoxic stress, promotes tumorigenesis. Here, we aimed to discuss the role of secondary metabolites along with BAs in maintaining immune-gut homeostasis and regulation of inflammation-driven tumorigenesis with emphasis on the classical Wnt/β-Catenin signaling pathway in colon cancer.